Vav2 catalysis-dependent pathways contribute to skeletal muscle growth and metabolic homeostasis - Sonia Rodríguez-Fdez (Nature Portfolio, 2020)
Skeletal muscle plays a key role in regulating systemic glucose and metabolic homeostasis. Here, the authors show that the catalytic activity of Vav2, an activator of Rho GTPases, modulates those processes by favoring the responsiveness of this tissue to insulin and related factors.